WIDOW STEREOTYPE IN THE ONLINE MEDIA NEWS - Dwi Ajeng Widarini (Jurnal Komunikasi & Media Digital, 2023)
This paper will focus on news on dream.co.id and tribunnews.com, which contain the keyword “widow”, for the period June 2023. This research aims to reveal the construction of reality in news stories about widows in online media. By using Sara Mills' critical analysis, which emphasizes two aspects, namely the position of the subject-object and the position of the reader, The method used in this research is qualitative, which is descriptive in nature. Women are often in the news with a gender construct. The clickbait-based news search system contributes to the perpetuation of stereotypes against widows in online media. These stereotypes portray widows as sensual, helpless objects who are in need of pity and are easily deceived by men, primarily because they are unable to engage in self-reflection.